Implementation of the Winnowing Algorithm in Detecting Plagiarism in Title and Abstract of Student's Final Project - Nasien, Dewi; Putra Yansen, Eka (IT Journal Research and Development, 2022)
In this modern era, technology has become more sophisticated. All information can be accessed quickly and efficiently. Nevertheless, when surfing the internet to search for information, people frequently find it almost similar and even have no different. Moreover, to news information content on the internet, similarities are found in final semester student research titles and abstracts as well. In preventing this, the researchers explored how to establish a website design by checking the similarity of titles and abstracts with winnowing method, which is exacted to complete examining the similarity of titles and abstracts on students' final assignments. The researchers applied dummy data obtained from Google Scholar for this study. The results revealed that the application of the winnowing method can aid in achieving similar results from the student's final assignments. It is deliberated as a benchmark for accepting a title and abstract at a university and reducing plagiarism.